Age limits of jumpers at the stage of preserving the highest sports skill are substantiated in article. - Sovenko S.P (Kharkov National Pedagogical University, 2011)
Presents data regarding the age to achieve maximum results, length of stay in the top ten athletes of the world and the dynamics of athletic performance of leading athletes, jumpers. The studies analyzed data on the dynamics of sport performance medalist Olympics 1988-2008 period. Proved that the age limit for athletes at the stage-divers maintain high sports are on average 27-33 years. Found that after the best athletic performance characteristic is to maintain them at a high level within 3% for another 3-4 years.